Odpowiedzi

2010-01-25T18:45:24+01:00
A) -3 (2a+2b+3) = -6a-6b-9
b) ( -2x+3y-5)* (-5) =10x-15y+25
c) o,7(10x-20y) = 7x-14y
d) 0,25x (8y-12z) =2xy-3xz
e) 3a(-5a-3b+2c) =-15a²-9ab+6ac
f) (4x-2y-7z) *( - 2x)= -8x²+4xy+14xz
2010-01-25T18:51:46+01:00
A) -3 (2a+2b+3) =-6a+6b+9
b) ( -2x+3y-5) *(-5) =10x-15y+25
c) o,7(10x-20y) =7x-14y
d) 0,25x (8y-12z) =2xy-3xz
e) 3a(-5a-3b+2c) =-15a kwadrat-9ab+6ac
f) (4x-2y-7z) *( - 2x)= -8xkwadrat+4xy+14xz
2010-01-25T18:58:14+01:00
A)-3 (2a+2b+3)=-6a-6b-9
b)(-2x+3y-5)*(-5)=10x-15y+25
c)0,7(10x-20y=7x-14y
d)0,25x(8y-12z)=2x-3z
e)3a(-5a-3b+2c)=-15a do kwadratu-9ab+6ac
f) (4x-2y-7z)*(-2x)=-8x do kwadratu+4xy+14xz